Motive8!: feasibility of a text messaging intervention to promote physical activity in knee osteoarthritis - Blake, Holly; Roberts, Anna L.; Batt, Mark E.; Moses, Jonathan P. (ClinMed International Library, 2015)
Aim: To develop and test the feasibility of using a SMS text messaging intervention to promote physical activity in patients with knee OA.